Development of innovative functional foods and nutraceuraticals. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2004)
Good nutrition influences health and wen being and may play a preventative role against many diseases. It is well-known that soya products such as soya milk drink. tempeh and tofu, carotene in oil palm. 85 well as lycopene in tomatoes may reduce the risk of cancer; probiotics and prebiotics create a healthy gut microflora; and unsaturated fatty acids and plant phytosterols are useful for cholesterol reduction. The health related aspects of food accelerate innovations in the food industry and have a high market potential.